Tailoring kappa/iota-hybrid carrageenan from Mastocarpus stellatus with desired gel quality through pre-extraction alkali treatment - Azevedo, Gabriela (2013)
Mastocarpus stellatus seaweeds were subjected to different alkali pre-treatments to investigate the effect of alkali type, concentration and treatment duration on the chemical structure and the gelling properties of extracted kappa/iota-hybrid carrageenan (KI). Increasing the concentration in KOH and the pretreatment time gives KI with lower amounts of nu-carrageenan units, which have a direct impact on the improved gelling properties. However, excessive KOH concentration and pre-treatment duration give KI with smaller molecular mass and depressed gel properties. NaOH is more efficient in converting nucarrageenan to iota-carrageenan, but no correlation between the chemical structure and gel properties was found. An interaction between the alkali concentration and the pre-treatment duration complicates the rationalization of NaOH efficiency. A set of KI with 60e75 mol% kappa-carrageenan and tailored gelling properties for a wide range of applications is delivered